Dampak Pengembangan Hidden Canyon Beji Guwang Sebagai Destinasi Wisata Terhadap Perekonomian Masyarakat Lokal Di Desa Guwang Kecamatan Sukawati Gianyar - Ayu Diva Septiyani Putri Sugianta; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
Tourism is designed to be a number one source of foreign exchange in Indonesia. But the development of toursm and tourist destination will definitely have an economic impact whether it’s positive impact or negative impact. As well as development in tourist destinationHidden Canyon Beji Guwang. This research aims to find out what is the participation of local community in the development of Hidden Canyon Beji Guwangand to find out what is the economic impactof it. The data used in this research is qualitative and quantitative data. Primary data source data and secondary data source. This research used descriptive qualitative method. Which is obtained through observation, in-depth interviews and documentation. Informant determination is done bypurposive sampling technique. The results of this research is tourist destinationHidden Canyon Beji Guwangmanagement derived entirely from the participation of local communities in Desa Guwang. Economic impact which is more dominantly felt by the local communities because the management system is only employs local people from Guwang Village whosemost of them are dropped out of school. Keywords: Economic Impact, Participation of Local Communities, Tourism Destination, Hidden Canyon Beji Guwang